Ten theories of religion - Pals, Daniel L. (New York : Oxford University Press, 2021)
'Why do human beings believe in divinities? Why do some seek eternal life, while others seek escape from recurring lives? Why do the beliefs and behaviors we typically call'religious' so deeply affect the human personality and so subtly weave their way through human society? Ideal as a supplementary text in introductory religion courses or as the main text in theory and method in religious studies or in sociology of religion courses, Ten Theories of Religion, Fourth Edition, offers an illuminating treatment of this controversial and fascinating subject'--
Revised edition of: Nine theories of religion. 2015.
Keywords: Religion -- Study and teaching -- History